2020
DOI: 10.1088/1742-6596/1470/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

Local wisdom value’s-based literacy education learning model in elementary school

Abstract: The lack of a model for promoting productive learning environments and a clear major value of choice to guide practice has resulted in the needs for this research. Values are important aspects of learning, yet they are not used to their fullest potential in educational practices in Indonesia. The primary objective for this study was to propose an appropriate model with application of local wisdom value in elementary school, and synthesized strategies for challenging the value for sustainable use in schools. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
0
8
0
3
Order By: Relevance
“…Science can develop with character education that is integrated with local wisdom in learning tools (Irwansyah et al 2020). The learning model developed by integrating local wisdom will encourage a positive climate in the classroom, a learning community, and maximize opportunities to learn (Lyesmaya, 2020). Ethno-pedagogy and local wisdom are seen as quite effective in introducing the noble values of the nation's culture, which can help build a nation's character based on social, culture, and environment (Mukhibat & Effendi, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Science can develop with character education that is integrated with local wisdom in learning tools (Irwansyah et al 2020). The learning model developed by integrating local wisdom will encourage a positive climate in the classroom, a learning community, and maximize opportunities to learn (Lyesmaya, 2020). Ethno-pedagogy and local wisdom are seen as quite effective in introducing the noble values of the nation's culture, which can help build a nation's character based on social, culture, and environment (Mukhibat & Effendi, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The development of school literacy is closely related to the habits that exist in the surrounding community. Local values are cultural concepts born from critical thinking in a region, there are also levels of moral development for students that are interrelated to build literacy based on local wisdom values (Lyesmaya et al, 2020). In connection with that, local wisdom activities through the integration of the School Literacy Movement (GLS) vary activities according to conditions at school, activities that refer to local wisdom form character for students (Farida Nugrahania, Ali Imron A, 2020).…”
Section: Integration Of Local Wisdom In School Literacymentioning
confidence: 99%
“…Previous research that has been conducted found that strengthening character education through literacy based on local wisdom is contained in the form of folklore products, song art, and religious holidays (Winangun, 2020). In addition, research that has been conducted on the learning model of literacy education based on local wisdom values in primary schools suggests that learning is designed to be collaborated with the literacy learning process in primary schools (Lyesmaya et al, 2020). And it was also found that integrating local wisdom in learning in several ways in schools such as in entrepreneurship learning is in accordance with the characteristics of entrepreneurship, namely: hard work, creativity, independence, and honesty (Komara & Adiraharja, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The new Ukrainian school must cultivate not only responsibility for oneself, but also for the development and well-being of the country and all mankind (Verkhovna Rada of Ukraine, 2016). Thus, the problem of moral education is relevant and needs empirical research (Ruyter, 2019), as well as a purposeful moral and characteristic goal of education -promote the realization of generally accepted moral values (Lyesmaya et al, 2020).…”
Section: Literary Reviewmentioning
confidence: 99%